Effect of Vajikaran Rasayana herbs in sexual behavior of old age rats - Sharma, Vikas; Chauhan, Nagendra S.; Patil, U. K.; Dixit, V.K. (Indian Journal of Natural Products, 2019)
Background: According to Indian Systems of Medicine, Spilanthes acmella (L.)Murr.Anacyclus pyrethrum DC, Pedalium murex Linn.is considered effective in the treatment of sexual deficiencies especially due to aging. Purpose: To assess the effect of ethanolic extracts of theAnacyclus pyrethrum roots, Spilanthes acmella flowers and Pedalium murex fruits in sexual behavior of old age rats Method:In the present study ethanolic extracts of theAnacyclus pyrethrum roots, Spilanthes acmella flowers and Pedalium murex fruits were investigatedon general mating pattern, penile erection and serum hormone levels of old age male Wistar albino rats and compared with sildenafil citrate and Testosterone. For assessment of sexual behavior, animals were divided into six groups of six male rats. All extracts (150 mg/kg body weight/day orally) and sildenafil citrate(5mg/kg body weight/day orally) and Testosterone (0.5mg /Kg b. w. i.m. in arachis oil twice weekly) (positive control) were administered for 28 days. The behavioral and sexual parameters were observed at day 0, 15 and 28 of drug treatment. Results: The orally administered extract had a positive effect on mounting frequency, intromission frequency and ejaculation frequency and the most significant effects (p< 0.05) were observed Anacyclus pyrethrum treatment. Apositive effect was also observed on the testosterone serum levels. Sildenafil citrate exhibited also a significant effect on penile erection, but no effect on hormone levels of rats was observed. Conclusion: The aphrodisiac potential of ethanolic extract of Anacyclus pyrethrum, Spilanthes acmella and Pedalium murex was demonstrated in-vivo. Study lends support to the traditional utilization Vajikaran Rasayana herbs as a sexual stimulating agent in old age.
Keywords: Aphrodisiac; Male sexual behavior; Anacyclus pyrethrum DC; Spilanthes acmella; Pedalium murex Linn